PRAKTEK PENGOBATAN SUKU SAKAI BATHIN SOBANGA - Febri Ramansyah Harahap; M Rawa El Amady (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2022)
This study discussed the eastern healing practice in Sakai Batin Sobanga at Sobanga Asal Hamlet, Bengkalis, Riau. Sakai tribe is well known in the community for its healing practices. Badike is a ritual that has been widely studied from various disciplines, while the ritual practices of other Sakai tribes are not widely known. This is a qualitative study with an ethnographic approach, in which the researchers stayed for two months in Kasumbu Ampai Village, Sobanga Hamlet, Mandau District, Bengkalis Regency, Riau. Data were taken through participatory observation and in-depth interviews with informants. The informants were bomo and several community leaders. The data were analyzed descriptively and then written in the form of narrative using Kalangie and Foster’s eastern healing theory to get a general trend. This study found that the medical practice in the Sakai Batin Sobanga tribe is an integral system, so that a ritual is precondition for the next one. Badike ritual cannot be carried out if personal healing ritual, tetomeh ritual, baulin and jungkul ritual have not been carried out. The Badike ritual is the last stage of the Sakai Tribal healing practice in Batin Sobanga. Religion-based healing and western medicine practices are also found in Batin Sobanga. Bomo is always open to his patients and gives them a space to go to a doctor or tuan guru. This research contributes to the anthropology of health, ethnomedicine, especially its novelty about the process of medical practice in the Sakai Tribe in Batin Sobanga.